Kiprah Pendongeng Sunda dalam Melestarikan Tradisi Lisan Masyarakat Sunda Abad Ke-20 - Dina Marliana; Agus Permana; A. Soheh Mukarrom (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the role of Sundanese storytellers in preserving the oral tradition of the Sundanese people in the 20th century by using historical methods. The historical methods used include heuristic stages, source criticism, interpretation, and historiography. At the heuristic stage, various sources in the form of radio recordings, local media archives, fairy tale transcripts, character interviews, and performance documentation were collected to trace the activities of Sundanese storytellers. The results of the analysis showed that Sundanese storytellers play an important role as a transmitter of cultural values, language keepers, as well as a link between tradition and society in the context of modernization. Through historical interpretation, it is found that storytellers not only maintain the traditional form of fairy tales, but also adapt to the development of media such as radio, tapes, and social media today. Thus expanding the range of Sundanese oral culture. The results of this study confirmed that the gait of Sundanese storytellers has become a significant factor in maintaining the sustainability of oral traditions as the cultural identity of the Sundanese people.